Sequence spaces and summability over valued fields - Natarajan, P. N. (Boca Raton : CRC Press, Taylor & Francis Group, 2020)
Sequence spaces and summability over valued fields is a research book aimed at research scholars, graduate students and teachers with an interest in Summability Theory both Classical (Archimedean) and Ultrametric (non-Archimedean). The book presents theory and methods in the chosen topic, spread over 8 chapters that seem to be important at research level in a still developing topic. Key Features Presented in a self-contained manner Provides examples and counterexamples in the relevant contexts Provides extensive references at the end of each chapter to enable the reader to do further research in the topic Presented in the same book, a comparative study of Archimedean and non-Archimedean Summability Theory Appeals to young researchers and experienced mathematicians who wish to explore new areas in Summability Theory The book is written by a very experienced educator and researcher in Mathematical Analysis particularly Summability Theory.
OCLC-licensed vendor bibliographic record.
Keywords: Linear topological spaces; Sequence spaces; Topological fields; Valued fields; MATHEMATICS / Functional Analysis; MATHEMATICS / Algebra / General